NbPIRIN promotes the protease activity of papain-like cysteine protease NbRD21 to inhibit Chinese wheat mosaic virus infection. - Kaili Zhong; Gecheng Xu; Jingjing Shi; Peng Liu; Aizhu Tu; Mila Wu; Jiaqian Liu; Jianping Chen; Jian Yang (PLoS Pathogens)
Papain-like cysteine proteases (PLCPs) play critical roles in regulating plant immunity against a range of pathogens and a series of cysteine protease inhibitors have been identified, however, relatively little research has been done on proteins that enhance the protease activity of PLCPs. Here, we identified a protein named NbPIRIN, the silencing of NbPIRIN promotes Chinese wheat mosaic virus (CWMV) infection, whereas the transgenic overexpression of NbPIRIN inhibits CWMV infection in Nicotiana benthamiana. Furthermore, we found that NbPIRIN interacts with papain-like cysteine protease (NbRD21) and increases its protease activity. We demonstrated that the silencing of NbRD21 significantly increased host susceptibility to CWMV infection, whereas the transgenic overexpression of NbRD21 increased host resistance. Interestingly, CWMV CRP was found to interact with both NbPIRIN and NbRD21, thus interfering with the interaction between NbPIRIN and NbRD21 and subsequently inhibiting the protease activity of NbRD21. Since wheat is the natural host of CWMV, we identified TaPIRIN and TaRD21 and found that they had functions similar to those of NbPIRIN and NbRD21 in the CWMV response. These results reveal a previously unreported offensive and defensive strategy between plants and viruses.